PENGARUH PELATIHAN DAN KOMPENSASI TERHADAP KINERJA PEGAWAI PADA DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KABUPATEN PANDEGLANG - Muhi Mukti; Robiatul Adawiyah (Universitas La Tansa Mashiro, 2019)
Some problems such as cooperation that is not well established, employees who are still not able to complete their tasks in a timely manner, lack of enthusiasm for the employees and less than optimal performance, can hamper and make work not run smoothly as it should. So this study aims to determine how the effe1ct of training and compensation on employee performance at the Public Works and Spatial Planning Office in Pandeglang Regency.In this study, the research method used is a quantitative method, and in taking the size of the number of samples using the Slovin formula. Testing of this study was carried out using a classic assumption test, then analyzed by correlation test and multiple linear regression tests using IBM Statistical Product and Service Solution (SPSS) Version 20.The results of the partial test (statistical test t) showed the Training variable with a significance level of 5% and the results of the SPSS Version 20 test showed, the significance value <0.05. This shows that H0 is rejected and the result of thus H1 is accepted because tcount>ttable. For the Compensaton variable shows, the significance value >0.05. This shows that H0 was accepted and the results of thus H2 was rejected because tcount<ttable. Significance test results simultaneously (statistical test f) significance level of 5% or 0.05 is smaller than the significance value of SPSS Version 20 output <0.05 then H0 is rejected so it can be said to be significant. And the results of Fcount>Ftable thus H3 is accepted.Based on the results of the study it can be seen that the Training has an influence on employee performance, while Compensation has no influence on employee performance. And simultaneously has an influence between the Training and Compensation variables on Employee Performance.